Participatory characterization of cocoa and livestock agri-food systems in Caquetá: A community perspective - Maya, Diana Lucía; Rodríguez, Luz Á; Álvarez, Javier Eduardo; Buitrago, Juliana (2024)
The department of Caquetá in the Colombian Amazon plays a crucial role in addressing greenhouse gas (GHG) emissions from food systems, primarily stemming from land use changes, such as the conversion of forests into pastures, and agricultural practices. Despite 72% of the department still being covered by forests, participatory research in two municipalities, Montañita and Belén de los Andaquíes, reveals a diverse agrifood landscape, focusing on cocoa and livestock. Utilizing participatory tools like productive profiles, social cartography, and vulnerability matrices, the study emphasizes the importance of supporting diversified systems with conservation and low-emission practices to enhance sustainability and contribute to food security. However, challenges exist, including the need for improved market conditions, incentivizing sustainable practices, and addressing infrastructural limitations. Additionally, the study highlights the necessity of reinforcing women's and youth's participation and decision-making in food systems to achieve more equitable and sustainable outcomes, given the existing gender disparities and youth migration issues.